CAMPUR KODE DAN ALIH KODE TAYANGAN MASTERCHEF INDONESIA SEASON 9 TAHUN 2022 PADA KANAL YOUTUBE MASTERCHEF INDONESIA - Fitriyani, Irma Rizqia; Wismanto, Agus; Septiana, Ika (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
Language is an element that plays an important role in communication between communities. The role of language as a means of communication in society is also bilingualism. Bilingualism itself means that a person can use two languages or two language codes. Therefore, in daily activities it is not uncommon for someone to do code mixing and code switching in their utterances. As is the case with the biggest cooking competition in Indonesia, MasterChef Indonesia. Apart from being a bilingual community, the MasterChef Indonesia competition program is internationally based, adapted from the Australian MasterChef event. Through this research, it will be explained how the use of code mixing and code switching that occurs in MasterChef Indonesia Season 9 2022 broadcasts on the MasterChef Indonesia YouTube Channel.